Durabilitas Mortar Polimer Termodifikasi Alami dengan Amylum dan Bahan Tambah Madu - Nanda Isdian Prasetyo; Gerald Arsa Adhiyaksa Abiyoga; Rr. M.I. Retno Susilorini; Budi Santosa (Universitas Katolik Soegijapranata Semarang, 2018)
The research aimed to investigate the durability of natural modified polymer mortar with amylum and honey admixture of aggressive environment that was modeled by 3 curing media, sea water, brakish water, and tidal flooding water. There were 855 specimens of mortar cubes with addition of amylum of 0,1%, 0,2%, 1%, 2%, and 5% and also honey of 0%, 0,03%, and 0,03%. All specimenswere cured and distributed into 3 curing medias for 7, 14, and 28 days. The result of this research met conclusion that optimum compressive strength was achieved by specimen with composition 0,1% amylum and 0,03% honey that was cured by sea water.